Cultivating not gatekeeping: a key leadership role in the creative process. Issue 1 (8th January 2021) - Katz, Joshua H; Herman, Geoffrey L; Johnson, Mark A; Loewenstein, Jeffrey
Abstract : Background Creativity and innovation are frequent features in healthcare discussions and proposals. A burgeoning area of research shows that evaluating proposals is a crucial juncture in the creative process. Leadership can make a substantial difference in how well the evaluation process does. Result Organisational leaders want creativity, yet often inadvertently act as gatekeepers and disproportionately reject creative proposals. We review research to provide guidance for leaders on how to cultivate creativity through improvements in the process of evaluating proposals.